Management of suspected viral encephalitis in adults--Association of British Neurologists and British Infection Association National Guidelines. - Solomon, T; Michael, B; Smith, P; Sanderson, F; Davies, N; Hart, I; Holland, M; Easton, A; Buckley, C; Kneen, R; Beeching, N (2012)
In the 1980s the outcome of patients with herpes simplex encephalitis was shown to be dramatically improved with aciclovir treatment. Delays in starting treatment, particularly beyond 48 h after hospital admission, are associated with a worse prognosis. Several comprehensive reviews of the investigation and management of encephalitis have been published. However, their impact on day-to day clinical practice appears to be limited. The emergency management of meningitis in children and adults was revolutionised by the introduction of a simple algorithm as part of management guidelines. In February 2008 a group of clinicians met in Liverpool to begin the development process for clinical care guidelines based around a similar simple algorithm, supported by an evidence base, whose implementation is hoped would improve the management of patients with suspected encephalitis.